Event Study on the Crash of Airasia Plane: A Study on Travel and Leisure Companies Listed at Malaysian Stock Market - Tatang Ary Gumanti Ary Gumanti; Enni Savitri; Nurul Wahidatun Nisa; Elok Sri Utami (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study analyzes the Malaysian stock market reaction in the event of the crash of AirAsia plane on 28 December 2014. The analysis is focused on the travel and leisure industry as the crash would affect more on this type of industry. A total of 15 companies met the selection criteria. The study uses the event study standard procedures in testing the proposed hypotheses. Results show that abnormal returns after the crash tend to decrease, yet no significant abnormal returns were found in the period before and after the event. Median abnormal return after the event is significantly higher than before the event at the traditional level. Another finding shows that there is no significant difference in trading volume activity between before and after the event.